Complex Rangeland Systems: Integrated Social-Ecological Approaches to Silvopastoralism - Plieninger, Tobias; Huntsinger, Lynn (Rangeland ecology & management, 2018)
Crossing disciplinary boundaries, particularly between social and ecological sciences, challenges those seeking to contribute to solving complex andmultidimensional environmental problems on rangelands. In this Special Issue we present a set of 13 papers that to varying degrees attempt to integrate, or bring together, diverse approaches across disciplines to understand silvopastoral systems. The papers are about rangelands in numerous countries and regions, including Spain, Estonia, Greece, Germany, Hungary, Italy, Portugal, Romania, the United States, Latin America, and Sweden. Silvopastoral systems provide ecosystemgoods and services important to communities, cultures, and society.Management deliberately exploits the diversity fostered by rangeland systems thatmix woody species with a well-developed herbaceous understory, offering a greater diversity of products, species, vegetation structural characteristics, and habitat components than either grassland or forest. Biodiversity often peaks at the intermediate levels of tree and shrub cover characteristic of silvopastoral systems. We introduce the papers grouped by four overarching topics: 1) typologies and scales, 2) social-ecological interactions, 3) integrated management, and 4) multiple knowledge systems. Unfortunately, silvopastoral systems often run afoul of ongoing intensification and simplification trends in agricultural production that reduce their economic and ecological resilience. Privately owned systems, the most common in this issue, are subject to the need for owner income. Finding ways to support the benefits of these systems for the public is difficult, as management traditions must be conserved as well as the land.We hope this issue illustrates the value of multifunctional systems and offers insights into how they work.